Thermoplastic oil-resistant sheath material for nuclear power station cable and preparation method of thermoplastic oil-resistant sheath material
By combining components such as block copolymer polypropylene and hydrogenated nitrile rubber, the problems of oil resistance, high temperature resistance, halogen-free low smoke flame retardancy of nuclear power plant cable sheathing materials have been solved. The stability and flame retardancy of the material in high temperature environment have been achieved, and the damage to mechanical properties caused by radiation crosslinking has been avoided.
Patent Information
- Application Number
- CN202511446881.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-11-25
AI Technical Summary
Existing technologies cannot simultaneously meet the comprehensive requirements of nuclear power plant cable sheath materials for oil resistance, high temperature resistance, halogen-free low smoke flame retardancy, and radiation resistance, and irradiation crosslinking leads to a decline in the mechanical properties of the materials.
It uses block copolymer polypropylene, hydrogenated nitrile rubber, active magnesium hydroxide and other components, and is processed through a specific crosslinking system and multi-step modification process to form a uniformly distributed "island phase" structure, which avoids radiation damage and improves compatibility and flame retardant effect.
It achieves oil resistance and flame retardancy of materials in high-temperature environments, maintains excellent mechanical properties, meets the long-term use requirements of nuclear power plant cables, and has low production costs.
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a thermoplastic oil-resistant sheathing material for nuclear power plant cables and its preparation method. Background Technology
[0002] As a critical transmission component of nuclear facilities, cables used in nuclear power plants must have sheath materials that simultaneously meet the requirements of halogen-free, low-smoke, flame-retardant, high-temperature, radiation-resistant, and oil-resistant properties under specific conditions.
[0003] In the prior art, to achieve oil resistance, the industry generally adopts the method of adding nitrile rubber to the sheath material. Because the cyano group in the nitrile rubber molecule has poor compatibility with oil molecules, it can effectively block oil penetration. However, this method has significant drawbacks: (1) Nitrile rubber is a polar elastomer, which has poor compatibility with halogen-free flame retardant systems and polyolefin matrices, resulting in uneven material dispersion, decreased mechanical properties, and easy cracking at low temperatures; (2) In order to improve the temperature resistance and crosslinking degree to enhance oil resistance, the prior art often relies on irradiation crosslinking process. However, irradiation will cause polymer chain breakage or excessive crosslinking, further reducing the elongation at break, which cannot meet the requirements of nuclear power plant cables.
[0004] In summary, existing technologies cannot simultaneously meet the comprehensive requirements of nuclear power plant cable sheathing materials for oil resistance, high temperature resistance, halogen-free low smoke flame retardancy, radiation resistance, and excellent mechanical properties. There is an urgent need for a new type of sheathing material that does not require radiation cross-linking and can balance various properties. Summary of the Invention
[0005] To address the problems existing in the prior art, a thermoplastic oil-resistant sheathing material for nuclear power plant cables and its preparation method are provided.
[0006] The technical solution adopted in this invention is: The first objective of this invention is to provide a thermoplastic oil-resistant sheathing material for nuclear power plant cables, comprising the following components by weight: 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.3-0.5 parts sulfur, 1-5 parts zinc oxide, 1-1.5 parts accelerator TT, 7 parts maleic anhydride-grafted polypropylene, 3 parts maleic anhydride-grafted ethylene-octene copolymer, 3-6 parts silicone masterbatch, 2-4 parts carbon black masterbatch, 180-220 parts activated magnesium hydroxide, 40-60 parts bismuth hydroxide, 8-16 parts sericite, 4-8 parts iron oxide, 1-3 parts primary antioxidant, 0.5-1.5 parts secondary antioxidant, and 3-6 parts octaphenylcyclotetrasiloxane.
[0007] Further, by mass parts, it includes the following components: 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.3-0.5 parts sulfur, 1-5 parts zinc oxide, 1-1.5 parts accelerator TT, 7 parts maleic anhydride grafted polypropylene, 3 parts maleic anhydride grafted ethylene-octene copolymer, 3-6 parts silicone masterbatch, 2-4 parts carbon black masterbatch, 180-220 parts activated magnesium hydroxide, 40-60 parts bismuth hydroxide, 8-16 parts sericite, 4-8 parts iron oxide, 1-3 parts primary antioxidant, 0.5-1.5 parts secondary antioxidant, and 3-6 parts octaphenylcyclotetrasiloxane.
[0008] Furthermore, the primary antioxidant is a hindered phenolic antioxidant, preferably one or two of antioxidant 1010 and antioxidant 1076; the secondary antioxidant is a phosphite antioxidant, preferably one or two of antioxidant 168 and antioxidant 626.
[0009] Furthermore, the silicone masterbatch is a blended masterbatch of silicone powder and polypropylene, wherein the mass fraction of silicone powder is 30%~50%; the carbon black masterbatch is a blended masterbatch of carbon black and polypropylene, wherein the mass fraction of carbon black is 40%~60%.
[0010] Furthermore, the active magnesium hydroxide has a particle size of 1~5 μm and a specific surface area of 10~20 m². 2 / g; The preparation method of this active magnesium hydroxide is as follows: (1) With a calcium content of 0.01-10 wt%, an average original particle size of 0.1-4 micrometers, an average aggregate particle size of 5-50 micrometers, and a specific surface area of 5-40 m², 2 Using calcium-containing agglomerated magnesium hydroxide with a main content of 85-97% as raw material, it is added to an aqueous solution containing 0.01-20wt% calcium removal agent and 0.01-20wt% dispersant to prepare a suspension with a solid content of 1-30wt%. Then, the suspension is stirred and reacted at 10-100℃ for 0.5-36 hours, filtered, washed, and dried to obtain dispersed high-purity magnesium hydroxide with a main content of ≥98.5wt%. (2) Dispersed high-purity magnesium hydroxide is placed in a vacuum furnace and heated to 300-700℃ at a rate of 0.05-30℃ / min in an air or nitrogen atmosphere, and calcined at a constant temperature for 1-24 hours to obtain a specific surface area of 100-800m². 2 / g of porous, highly active magnesium oxide; (3) Porous, highly active magnesium oxide is added to an aqueous solution containing 0.001-20 wt% surfactant to prepare a suspension with a solid content of 1-40 wt%. Then, it is stirred and hydrated at 10-150℃ for 0.5-10 hours. After filtration, washing, and drying, an average original particle size of 1-5 μm and a specific surface area of 10-20 m² are obtained. 2 High-purity, highly active magnesium hydroxide with a main content ≥99wt% / g.
[0011] Furthermore, the sericite has a particle size of 2000-3000 mesh; the iron oxide is α-iron oxide with a particle size of 0.5-2 μm.
[0012] Another object of the present invention is to provide a method for preparing a thermoplastic oil-resistant sheath material for nuclear power plant cables, comprising the following steps: Step 1: Weigh the raw materials of each component according to the formula ratio; Step 2: After adding block copolymer polypropylene to a mixer at a temperature of 140~160℃ for melt mixing, add hydrogenated nitrile rubber, sulfur, zinc oxide, and accelerator TT. After melt mixing for 5~10 minutes, add the remaining raw materials and mix for 10~15 minutes to obtain the melt material. Step 3: Add the molten material obtained in Step 2 to a twin-screw extruder, extrude and granulate it at a temperature of 160~180℃, and air cool it to obtain the final product.
[0013] Compared with existing technologies, the thermoplastic oil-resistant sheathing material for nuclear power plant cables and its preparation method provided by this invention have the following advantages: (1) The sheath material of the present invention uses block copolymer polypropylene. This material relies on high crystallinity to resist molecular chain creep under high temperature environment, ensuring that the material can withstand the working temperature of nuclear power plant for a long time. At the same time, it retains good toughness by means of flexible chain segments, avoiding the material from becoming brittle and hard due to high temperature resistance requirements; thus, there is no need to enhance the temperature resistance through irradiation, fundamentally avoiding the damage to the mechanical properties of the material by the irradiation process. (2) The hydrogenated nitrile rubber in the sheath material of the present invention has a high saturation characteristic, which not only retains the barrier ability of cyano groups to oily substances and achieves excellent oil resistance, but also, when combined with a specific "selective crosslinking" system (sulfur, zinc oxide and accelerator TT work together), can precisely control the crosslinking reaction range, so that HNBR forms a dispersed "island phase" structure and is evenly distributed in the "marine phase" matrix composed of PP; this combination effectively improves the compatibility between the oil-resistant component and the matrix, and avoids problems such as insufficient oil resistance and poor thermal stability caused by poor compatibility; (3) The active magnesium hydroxide in the raw material of the present invention is processed by a multi-step modification process, including acid washing to remove impurities, calcination to create pores and surface activation, which significantly improves its compatibility with the organic matrix. At the same time, it is combined with bismuth hydroxide to form a synergistic flame retardant system. During the combustion process, bismuth hydroxide first absorbs heat and inhibits the initial combustion through dehydration. Then, it works together with active magnesium hydroxide to promote the formation of a dense flame retardant carbon layer and enhance the overall flame retardant effect. (4) The preparation process of this invention is simple and easy to operate, requiring no complex equipment or special processes. The raw materials are all industrially available products, resulting in low production costs and stable production capacity, which meets the needs of large-scale production of nuclear power plant cables. Detailed Implementation
[0014] The present invention will be further described below through specific embodiments, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not depart from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0015] Unless otherwise specified, the methods used in the following examples and comparative examples are all prior art; reagents not specifically mentioned are conventional reagents, all of which can be purchased from conventional reagent manufacturers and distributors. Information such as the manufacturers or CAS numbers of some raw materials is as follows: Block copolymer polypropylene, purchased from Suzhou Hongmingyang Plastics Co., Ltd.; Hydrogenated nitrile butadiene rubber was purchased from Shandong Dawn Special Elastomer Materials Co., Ltd. Sulfur was purchased from Shandong Yiguang Chemical Co., Ltd. Zinc oxide was purchased from Weifang Aolong Zinc Industry Co., Ltd. Accelerator TT was purchased from Shanghai Chengjin Chemical Co., Ltd. Maleic anhydride-grafted polypropylene was purchased from Nanjing Feiteng New Material Technology Co., Ltd. Maleic anhydride-grafted ethylene-octene copolymer was purchased from Wuxi Yiyuan New Material Technology Co., Ltd. Silicone masterbatch was purchased from Chengdu Silike Technology Co., Ltd. Carbon black was purchased from Shandong Kasong New Materials Co., Ltd. Polypropylene, CAS No. 9003-07-0, was purchased from Tiandingfeng Polypropylene Materials Technology Co., Ltd. Bismuth hydroxide, CAS No. 10361-43-0, was purchased from Shandong Jinshengtai Chemical Co., Ltd. Sericite, purchased from Chuzhou Baota Sericite Mining Co., Ltd.; Iron oxide was purchased from Zibo Baoyan Chemical Co., Ltd. Octaphenylcyclotetrasiloxane, CAS No. 546-56-5, was purchased from Jinan World Chemical Co., Ltd. Antioxidant 1010, CAS number 6683-19-8; Antioxidant 1076, CAS number 2082-79-3; Antioxidant 168, CAS number 31570-04-4; Antioxidant 626, CAS number 26741-53-7.
[0016] Example 1 A thermoplastic oil-resistant sheathing material for nuclear power plant cables, comprising the following components by mass parts (1000g / part): 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.3 parts sulfur, 5 parts zinc oxide, 1 part accelerator TT, 7 parts maleic anhydride-grafted polypropylene, 3 parts maleic anhydride-grafted ethylene-octene copolymer, 3 parts silicone masterbatch, 4 parts carbon black masterbatch, 220 parts activated magnesium hydroxide, 40 parts bismuth hydroxide, 8 parts sericite, 8 parts iron oxide, 1 part primary antioxidant, 1.5 parts secondary antioxidant, and 3 parts octaphenylcyclotetrasiloxane.
[0017] A method for preparing a thermoplastic oil-resistant sheath material for nuclear power plant cables includes the following steps: Step 1: Weigh the raw materials of each component according to the formula ratio; Step 2: After adding block copolymer polypropylene to a mixer at 150°C for melt mixing, add hydrogenated nitrile rubber, sulfur, zinc oxide, and accelerator TT. After melt mixing for 5-10 minutes, add the remaining raw materials and mix for 10-15 minutes to obtain the melt material. Step 3: Add the molten material obtained in Step 2 to a twin-screw extruder, extrude and granulate it at a temperature of 160℃, and then air-cool it to obtain the final product.
[0018] The main antioxidant is antioxidant 1010, the auxiliary antioxidant is antioxidant 168, the sericite is ultrafine sericite powder with a particle size of 2500 mesh, the iron oxide is α-iron oxide with a particle size of 0.5 μm, the silicone masterbatch is a blend of silicone powder and polypropylene, wherein the silicone powder has a mass fraction of 50%, and the carbon black masterbatch is a blend of carbon black and polypropylene, wherein the carbon black has a mass fraction of 40%.
[0019] The particle size of the active magnesium hydroxide is 5 μm, and the specific surface area is 10 m². 2 / g; The preparation method of this active magnesium hydroxide is as follows: Weigh 100 grams of calcium-containing agglomerated magnesium hydroxide raw material (calcium content 10wt%, average original particle size 0.1 micrometers, average agglomerated particle size 5 micrometers, specific surface area 40m²). 2 / g, magnesium hydroxide with a main content of 85wt%), was added to an aqueous solution containing 0.01wt% citric acid and 20wt% potassium chloride to prepare a suspension with a solid content of 1wt%. The suspension was then stirred at 10℃ (800 rpm) for 0.5 hours, filtered, washed, and dried (110℃, 1 hour) to obtain dispersed high-purity magnesium hydroxide with a main content of 98.5wt%. Dispersed high-purity magnesium hydroxide was placed in a vacuum furnace (vacuum degree 10). -3 Pa), heated to 300℃ in air at a rate of 0.05℃ / min, and calcined at this temperature for 1 hour to obtain a specific surface area of 800m². 2 / g porous active magnesium oxide; the above magnesium oxide was added to an aqueous solution containing 0.001wt% sodium dodecylbenzenesulfonate to prepare a suspension with a solid content of 1wt%, and hydrated and converted by stirring at 10℃ (800 rpm) for 0.5 hours. After filtration, washing, and drying (80℃, 6 hours), an average original particle size of 0.1 μm, an average agglomerated particle size of 0.2 μm, and a specific surface area of 500 μm were obtained. 2 / g, active magnesium hydroxide with a main content of 99wt%.
[0020] Example 2 A thermoplastic oil-resistant sheathing material for nuclear power plant cables, comprising the following components by weight (2000g / part): 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.5 parts sulfur, 1 part zinc oxide, 1.5 parts accelerator TT, 7 parts maleic anhydride-grafted polypropylene, 3 parts maleic anhydride-grafted ethylene-octene copolymer, 6 parts silicone masterbatch, 2 parts carbon black masterbatch, 180 parts activated magnesium hydroxide, 60 parts bismuth hydroxide, 16 parts sericite, 4 parts iron oxide, 3 parts primary antioxidant, 0.5 parts secondary antioxidant, and 6 parts octaphenylcyclotetrasiloxane.
[0021] A method for preparing a thermoplastic oil-resistant sheath material for nuclear power plant cables includes the following steps: Step 1: Weigh the raw materials of each component according to the formula ratio; Step 2: After adding block copolymer polypropylene to a mixer at 160℃ for melt mixing, add hydrogenated nitrile rubber, sulfur, zinc oxide, and accelerator TT. After melt mixing for 5-10 minutes, add the remaining raw materials and mix for 10-15 minutes to obtain the melt material. Step 3: Add the molten material obtained in Step 2 to a twin-screw extruder, extrude and granulate it at a temperature of 180℃, and then air-cool it to obtain the final product.
[0022] The main antioxidant is a mixture of antioxidant 1010 and antioxidant 1076 in a mass ratio of 1:1; the auxiliary antioxidant is antioxidant 626; the sericite is ultrafine sericite powder with a particle size of 2000 mesh; the iron oxide is α-iron oxide with a particle size of 2μm; the silicone masterbatch is a blend of silicone powder and polypropylene, wherein the silicone powder mass fraction is 30%; and the carbon black masterbatch is a blend of carbon black and polypropylene, wherein the carbon black mass fraction is 60%.
[0023] The particle size of the active magnesium hydroxide is 1 μm, and the specific surface area is 20 m². 2 / g; The preparation method of this active magnesium hydroxide is as follows: Weigh 100 grams of calcium-containing agglomerated magnesium hydroxide raw material (calcium content 0.01 wt%, average original particle size 4 micrometers, average agglomerated particle size 50 micrometers, specific surface area 5 m²). 2(g, magnesium hydroxide with a main content of 97wt%) was added to an aqueous solution containing 20wt% ethylenediaminetetraacetic acid, 0.01wt% potassium chloride, and 5wt% sodium hexametaphosphate to prepare a suspension with a solid content of 30wt%. The suspension was then stirred at 100℃ (50 rpm) for 36 hours, filtered, washed, and dried (80℃, 6 hours) to obtain dispersed high-purity magnesium hydroxide with a main content of 98.8wt%. The dispersed high-purity magnesium hydroxide was then placed in a vacuum furnace (vacuum degree 10). 4 Pa), heated to 700℃ at 30℃ / min in a nitrogen atmosphere, and calcined at that temperature for 24 hours to obtain a specific surface area of 100m². 2 / g porous active magnesium oxide; the above magnesium oxide was added to an aqueous solution containing 20wt% fatty acid polyoxyethylene ether to prepare a suspension with a solid content of 40wt%, and hydrated and converted by stirring at 150℃ (50 rpm) for 10 hours. After filtration, washing and drying (80℃, 6 hours), an average original particle size of 4 μm, an average aggregate particle size of 4 μm and a specific surface area of 60 μm were obtained. 2 High-purity, highly active magnesium hydroxide product with a main content of 99.8wt% per gram.
[0024] Example 3 A thermoplastic oil-resistant sheathing material for nuclear power plant cables, comprising the following components by mass parts (2000g / part): 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.4 parts sulfur, 3 parts zinc oxide, 1.2 parts accelerator TT, 7 parts maleic anhydride-grafted polypropylene, 3 parts maleic anhydride-grafted ethylene-octene copolymer, 5 parts silicone masterbatch, 3.5 parts carbon black masterbatch, 195 parts activated magnesium hydroxide, 52 parts bismuth hydroxide, 12 parts sericite, 6 parts iron oxide, 2 parts primary antioxidant, 1 part secondary antioxidant, and 5 parts octaphenylcyclotetrasiloxane.
[0025] A method for preparing a thermoplastic oil-resistant sheath material for nuclear power plant cables includes the following steps: Step 1: Weigh the raw materials of each component according to the formula ratio; Step 2: After adding block copolymer polypropylene to a mixer at 140℃ for melt mixing, add hydrogenated nitrile rubber, sulfur, zinc oxide, and accelerator TT. After melt mixing for 5-10 minutes, add the remaining raw materials and mix for 10-15 minutes to obtain the melt material. Step 3: Add the molten material obtained in Step 2 to a twin-screw extruder, extrude and granulate it at a temperature of 170℃, and then air-cool it to obtain the final product.
[0026] The main antioxidant is antioxidant 1076, and the auxiliary antioxidants are antioxidant 168 and antioxidant 626 mixed in a mass ratio of 1:3; the sericite is ultrafine sericite powder with a particle size of 3000 mesh; the iron oxide is α-iron oxide with a particle size of 1.5 μm; the silicone masterbatch is a blend of silicone powder and polypropylene, wherein the silicone powder mass fraction is 40%; and the carbon black masterbatch is a blend of carbon black and polypropylene, wherein the carbon black mass fraction is 50%.
[0027] The active magnesium hydroxide has a particle size of 5 μm and a specific surface area of 15 m². 2 / g; The preparation method of this active magnesium hydroxide is as follows: Weigh 100 grams of calcium-containing agglomerated magnesium hydroxide raw material (calcium content 5wt%, average original particle size 2 micrometers, average agglomerated particle size 15 micrometers, specific surface area 35m²). 2 (g, magnesium hydroxide with a main content of 92wt%) was added to an aqueous solution containing 10wt% sodium triacetate, 2wt% tartaric acid, and 0.5wt% magnesium chloride to prepare a suspension with a solid content of 20wt%. The suspension was then stirred at 90℃ (450 rpm) for 3 hours, filtered, washed, and dried (90℃, 2 hours) to obtain dispersed high-purity magnesium hydroxide with a main content of 98.6wt%. The dispersed high-purity magnesium hydroxide was then placed in a vacuum furnace (vacuum degree 10). -2 Pa), heated to 500℃ at a rate of 20℃ / min in a nitrogen atmosphere, and calcined at this temperature for 14 hours to obtain a specific surface area of 300m². 2 / g porous active magnesium oxide; the above magnesium oxide was added to an aqueous solution containing 12wt% sodium carboxymethyl starch and 5wt% sodium stearate to prepare a suspension with a solid content of 20wt%. The suspension was hydrated and converted by stirring at 60℃ (350 rpm) for 1 hour, then filtered, washed, and dried (100℃, 2 hours) to obtain an average original particle size of 2 μm, an average aggregate particle size of 6 μm, and a specific surface area of 160 μm. 2 High-purity, highly active magnesium hydroxide product with a main content of 99.2wt% per gram.
[0028] Comparative Example 1 The difference from Example 3 is that ordinary industrial-grade magnesium hydroxide (unactivated, particle size 5 μm, specific surface area 15 m²) was used. 2 (g) replaces active magnesium hydroxide, with the amount of raw materials remaining unchanged; other steps and preparation processes are the same as in Example 3.
[0029] Comparative Example 2 The difference from Example 3 is that the hydrogenated nitrile rubber in the raw materials is replaced with nitrile rubber, while the other steps and preparation process are the same as in Example 3.
[0030] Comparative Example 3 The difference from Example 3 is that sulfur in the raw materials is removed, while the other steps and preparation process are the same as in Example 3.
[0031] Comparative Example 4 The difference from Example 3 is that accelerator M replaces accelerator TT and octaphenylcyclotetrasiloxane in the raw materials is removed, while the other steps and preparation process are the same as in Example 3.
[0032] Experimental Example: Performance Testing 1. Test materials: Thermoplastic oil-resistant sheathing material prepared in the embodiments and comparative examples of this invention.
[0033] 2. Test methods: Refer to Table 1.
[0034] Table 1 Detection categories Testing items Implementation Standards Indicator Requirements Mechanical properties Tensile strength before aging GB / T 2951-2008 ≥10.5MPa Elongation at break before aging GB / T 2951-2008 ≥180% thermal aging performance Change rate of tensile strength after heat aging at 110℃ for 240 hours GB / T 2951-2008 ≤±25% Change rate of elongation at break after heat aging at 110℃ for 240 hours GB / T 2951-2008 ≤±25% thermal life 90℃ thermal life IEC 60216-1:2001 ≥60 years Radiation resistance 60Co-γ ray irradiation IEC 61244:2013 375kGy Rate of change of tensile strength after irradiation IEC 61244:2013 ≤±30% Oil resistance Change in tensile strength after immersion in IRM902 oil (100℃×72h) GB / T 1690-2010 ≤±20% Change in elongation at break after immersion in IRM902 oil (100℃×72h) GB / T 1690-2010 ≤±20% Volume expansion rate after oil immersion GB / T 1690-2010 ≤8% Flame retardant properties Oxygen Index (LOI) GB / T 2406.2-2009 ≥30% Flame smoke density (Dmy) GB / T 8323.2-2008 ≤100 Flameless smoke density (Dmw) GB / T 8323.2-2008 ≤350 HCl+HBr content GB / T 17650.2-1998 ≤0.5% (not detected) Low temperature performance Elongation at break under tensile stress at -35℃ GB / T 2951-2008 ≥30% Number of samples that failed due to impact embrittlement at -35℃ (30 samples) GB / T 5470-2008 ≤15 / 30 3. The test results are shown in Table 2.
[0035] Table 2. Performance test results of the sheathing materials obtained in the examples and comparative examples. Testing items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Mechanical properties Tensile strength before aging (MPa) 12.8 13.2 135 10.2 9.8 11.5 10.8 Elongation at break before aging (%) 215 222 228 175 160 190 182 thermal aging performance Tensile strength change rate (%) +4 +3 +3 -18 -22 -10 -15 Change in elongation at break (%) -7 -6 -6 -32 -38 -25 -30 thermal life 90℃ thermal life (years) 80.5 80.8 81.2 45.5 42.0 58.3 52.1 Radiation resistance 60Co-γ ray irradiation 2300kGy 2300kGy 2300kGy 500kGy 375kGy 525kGy 375kGy Change rate of tensile strength after irradiation (%) -5 -4 -4 -12 -25 -8 -18 Oil resistance Tensile strength change rate (%) +6 +5 +5 +8 -35 -28 -32 Change in elongation at break (%) -9 -8 -8 -15 -42 -35 -38 Volume expansion rate (%) 4.2 4.0 4.0 5.5 12.8 10.5 11.2 Flame retardant properties Oxygen Index (LOI) (%) 36.5 37.8 38.2 28.5 35.2 36.0 34.5 Flame smoke density (Dmy) 82 80 78 95 85 83 88 Flameless smoke density (Dmw) 158 155 152 280 170 165 185 Low temperature performance Elongation at break (%) at -35℃ 65 66 68 42 35 50 45 As shown in Table 2, the high-temperature halogen-free flame-retardant sheath material obtained in the embodiments of the present invention exhibits good performance in all test results, demonstrating excellent thermoplasticity, oil resistance, flame retardancy, and mechanical properties; while the performance of each comparative example is affected to varying degrees.
[0036] The specific analysis is as follows: The sheath material of this invention uses block copolymer polypropylene. This material relies on high crystallinity to resist molecular chain creep under high temperature environment, ensuring that the material can withstand the operating temperature of nuclear power plant for a long time. At the same time, it retains good toughness with the help of flexible segments, avoiding the material from becoming brittle and hard due to high temperature resistance requirements. Therefore, there is no need to enhance the temperature resistance through irradiation, fundamentally avoiding the damage to the mechanical properties of the material by the irradiation process. The hydrogenated nitrile butadiene rubber in the sheath material of this invention has a high saturation characteristic, which not only retains the barrier ability of the cyano group to oil substances, achieving excellent oil resistance, but also, when combined with a specific "selective crosslinking" system (sulfur, zinc oxide and accelerator TT working together), can precisely control the crosslinking reaction range, so that HNBR forms a dispersed "island phase" structure, which is uniformly distributed in the "marine phase" matrix composed of PP. This combination effectively improves the compatibility between the oil-resistant component and the matrix, avoiding problems such as insufficient oil resistance and poor thermal stability caused by poor compatibility. The active magnesium hydroxide in the raw material of this invention undergoes a multi-step modification process, including acid washing to remove impurities, calcination to create pores and surface activation, which significantly improves its compatibility with the organic matrix. At the same time, it is combined with bismuth hydroxide to form a synergistic flame retardant system. During combustion, bismuth hydroxide first absorbs heat and inhibits initial combustion through dehydration. Subsequently, it works together with active magnesium hydroxide to promote the formation of a dense flame-retardant char layer and enhance the overall flame retardant effect.
[0037] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A thermoplastic oil-resistant sheathing material for nuclear power plant cables, characterized in that, The composition by weight is as follows: 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.3-0.5 parts sulfur, 1-5 parts zinc oxide, 1-1.5 parts accelerator TT, 7 parts maleic anhydride grafted polypropylene, 3 parts maleic anhydride grafted ethylene-octene copolymer, 3-6 parts silicone masterbatch, 2-4 parts carbon black masterbatch, 180-220 parts activated magnesium hydroxide, 40-60 parts bismuth hydroxide, 8-16 parts sericite, 4-8 parts iron oxide, 1-3 parts primary antioxidant, 0.5-1.5 parts secondary antioxidant, and 3-6 parts octaphenylcyclotetrasiloxane.
2. The thermoplastic oil-resistant sheath material for nuclear power plant cables as described in claim 1, characterized in that, The composition by weight is as follows: 60 parts block copolymer polypropylene, 30 parts hydrogenated nitrile rubber, 0.3-0.5 parts sulfur, 1-5 parts zinc oxide, 1-1.5 parts accelerator TT, 7 parts maleic anhydride grafted polypropylene, 3 parts maleic anhydride grafted ethylene-octene copolymer, 3-6 parts silicone masterbatch, 2-4 parts carbon black masterbatch, 180-220 parts activated magnesium hydroxide, 40-60 parts bismuth hydroxide, 8-16 parts sericite, 4-8 parts iron oxide, 1-3 parts primary antioxidant, 0.5-1.5 parts secondary antioxidant, and 3-6 parts octaphenylcyclotetrasiloxane.
3. The thermoplastic oil-resistant sheath material for nuclear power plant cables as described in claim 1, characterized in that, The primary antioxidant is a hindered phenolic antioxidant, preferably one or two of antioxidant 1010 and antioxidant 1076; the secondary antioxidant is a phosphite antioxidant, preferably one or two of antioxidant 168 and antioxidant 626.
4. The thermoplastic oil-resistant sheath material for nuclear power plant cables as described in claim 1, characterized in that, The silicone masterbatch is a blend of silicone powder and polypropylene, wherein the silicone powder has a mass fraction of 30% to 50%; the carbon black masterbatch is a blend of carbon black and polypropylene, wherein the carbon black has a mass fraction of 40% to 60%.
5. The thermoplastic oil-resistant sheathing material for nuclear power plant cables as described in claim 1, characterized in that, The active magnesium hydroxide has a particle size of 1~5μm and a specific surface area of 10~20m². 2 / g; The preparation method of this active magnesium hydroxide is as follows: (1) With a calcium content of 0.01-10 wt%, an average original particle size of 0.1-4 micrometers, an average aggregate particle size of 5-50 micrometers, and a specific surface area of 5-40 m², 2 Using calcium-containing agglomerated magnesium hydroxide with a main content of 85-97% as raw material, it is added to an aqueous solution containing 0.01-20wt% calcium removal agent and 0.01-20wt% dispersant to prepare a suspension with a solid content of 1-30wt%. Then, the suspension is stirred and reacted at 10-100℃ for 0.5-36 hours, filtered, washed, and dried to obtain dispersed high-purity magnesium hydroxide with a main content of ≥98.5wt%. (2) Dispersed high-purity magnesium hydroxide is placed in a vacuum furnace and heated to 300-700℃ at a rate of 0.05-30℃ / min in an air or nitrogen atmosphere, and calcined at a constant temperature for 1-24 hours to obtain a specific surface area of 100-800m². 2 / g of porous, highly active magnesium oxide; (3) Porous, highly active magnesium oxide is added to an aqueous solution containing 0.001-20 wt% surfactant to prepare a suspension with a solid content of 1-40 wt%. Then, it is stirred and hydrated at 10-150℃ for 0.5-10 hours. After filtration, washing, and drying, an average original particle size of 1-5 μm and a specific surface area of 10-20 m² are obtained. 2 High-purity, highly active magnesium hydroxide with a main content ≥99wt% / g.
6. The high-temperature halogen-free flame-retardant cable material for nuclear power plant cables as described in claim 1, characterized in that, The sericite has a particle size of 2000-3000 mesh; the iron oxide is α-iron oxide with a particle size of 0.5-2 μm.
7. A method for preparing a thermoplastic oil-resistant sheathing material for nuclear power plant cables as described in any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Weigh the raw materials of each component according to the formula ratio; Step 2: After adding block copolymer polypropylene to a mixer at a temperature of 140~160℃ for melt mixing, add hydrogenated nitrile rubber, sulfur, zinc oxide, and accelerator TT. After melt mixing for 5~10 minutes, add the remaining raw materials and mix for 10~15 minutes to obtain the melt material. Step 3: Add the molten material obtained in Step 2 to a twin-screw extruder, extrude and granulate it at a temperature of 160~180℃, and air cool it to obtain the final product.